Managing Change in Banking Organisations - Ferenc Farkas (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Banks and credit institutions must be managed in order to ensure that they adapt to ever-changing social needs and consumer expectations. This is an everyday lesson, but to be honest, such teachings do not say much. Practising professionals in the banking sector need something more specific and practical to be able to manage changes effectively. The findings of this paper are based on desk research and field research. Empirical evidence is provided by the application of change management models of other sectors, for the banking sector. The goal of this paper is to enlarge the relevant knowledge that is needed more than ever by the Hungarian banking sector in order to tackle the challenges it faces. And experiences show that the knowledge base available is rather limited. Since change management has never made a special attempt to resolve the organisational changes of the banking sector neither on the international nor on the domestic scene, and because references to banking organisations are few, it is also goal of this paper to show Hungarian and international mini cases and literature examples where the change management was implemented successfully and that offer lessons for other organizations.
Keywords: G21; 330; banking organizations; credit institutions; change management; knowledge base; Hungarian and international mini cases